RESPONSE OF SOIL AND FOLIAR APPLICATION OF SILICON AND MICRO NUTRIENTS ON LEAF NUTRIENT STATUS OF SAPOTA - K. A. LALITHYA; H. P. BHAGYA; K. BHARATHI; HIPPARAGI, KULAPATI (The Bioscan, 2014)
The field experiment was conducted to know the response of soil and foliar application of silicon and micronutrients on nutrient status of sapota at College of Horticulture Mudigere, Chikamagalur district during the year 20102012. Silicon sources like potassium silicate and calcium silicate and micronutrient contents like solubor and kiecite –G were used. Macro nutrients like nitrogen (1.583 %), phosphorous (0.175 %) and the potassium (1.20 %) and silicon content (1.20 %) in leaf were recorded highest with potassium silicate spray with 8 ml per litre. Whereas micronutrient content has not increased considerably with respect to application of silicon sources. The maximum content of iron (179.89 ppm), copper (7.61 ppm), zinc (35.13 ppm) and manganese (91.16 ppm) was recorded in the leaf due to foliar spray of micronutrients at 4 ml per litre. As macro nutrient and silicon content was more in the treatment with foliar application of potassium silicate at 8 ml per litre resulted in more yield and quality of fruits.